Synthesis and Characterization of Nanostructured Blends of Epoxy Resin and Block Copolymers - Pandit, Rajesh; Berkessel, Albrecht; Lach, Ralf; Grellmann, Wolfgang; Adhikari, Rameshwar (Nepal Journal of Science and Technology, 2013)
Polystyrene–polybutadiene block copolymers having different molecular architectures were epoxidized by using meta-chloroperoxybenzoic acid (MCPBA). Then, the blends with epoxy resin (diglycidyl ether of bisphenol-A; DGEBA) and their nanocomposites with boehmite and layered silicate nanofiller in presence of methylene dianiline (MDA) as a hardener were prepared. The epoxidized copolymers and the composites were characterized by Fourier transform infrared (FTIR) spectroscopy and microindentation technique. In this way, it was possible to tune the morphology of the nanostructured blends of the epoxy resin using the functionalized block copolymer as the template. The presence of nanostructured morphology was attested by the optical transparency of the blends as well as of the composites with nanofiller. The microhardness properties were improved by the incorporation of the nanoparticles, viz. boehmite and layered silicate. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 81-88 DOI: http://dx.doi.org/10.3126/njst.v13i1.7445